ZIF-8-Embedded Cation-Exchange Membranes with Improved Monovalent Ion Selectivity for Capacitive Deionization - Eui-Gyu Han; Ji-Hyeon Lee; Moon-Sung Kang (Membranes)
Membrane capacitive deionization (MCDI) is an electrochemical ion separation process that combines ion-exchange membranes (IEMs) with porous carbon electrodes to enhance desalination efficiency and address the limitations of conventional capacitive deionization (CDI). In this study, a cation-exchange membrane (CEM) embedded with a metal–organic framework (MOF) was developed to effectively separate monovalent and multivalent cations in influent solutions via MCDI. To fabricate CEMs with high monovalent ion selectivity, ZIF-8 was incorporated into sulfonated poly(2,6-dimethyl-1,4-phenylene oxide) (SPPO) at various weight ratios. The resulting membranes were systematically characterized using diverse electrochemical methods. The ZIF-8-embedded CEMs demonstrated a sieving effect based on differences in ion size and hydration energy, achieving excellent permselectivity for monovalent ions. MCDI tests using the prepared CEMs showed a Na+ ion removal rate exceeding 99% in Na+/Mg2+ and Na+/Ca2+ mixed feed solutions, outperforming a commercial membrane (CSE, Astom Corp., Tokyo, Japan), which achieved a removal rate of 94.1%. These findings are expected to provide valuable insights for advancing not only MCDI but also other electro-membrane processes capable of selectively separating specific ions.